El enfoque empírico en la intervención del trabajo social en la corriente del estado de bienestar - Carvajal Saldarriaga, Ángel Eduardo (My University, 2021)
The fundamental aspects of the empirical approach and its application in Social Work have historically allowed us to go through the time of antiquity; and this profession in one way or another has made a presence on the world stage. Social Work was born with a mission for society, to promote social change, resolve conflicts and carry out other work that is necessary between the group or people to increase the well-being of all people in society. The purpose of this essay is to reflect on the man who experiences. He is a man who knows, his lived experiences to a great extent lead him to the empirical approach, the main theme of the essay, which allows us to recognize him as a man fruit of experience. Making a comprehensive reading of the presented essay you will find that the fundamental aspects of empiricism are valid today and can be experienced differently as long as the empirical aspect and the theoretical process validate the facts in their explanatory part. As in the case of education, empirical processes are privileged in the teaching-learning process.
Los aspectos fundamentales del enfoque empírico y su aplicación en el Trabajo Social han permitido recorrer, históricamente, el tiempo de la antigüedad; y esta profesión de una y otra manera ha hecho presencia en el escenario mundial. El Trabajo Social nació con una misión para la sociedad, fomentar el cambio social, resolver conflictos y desempeñar otra labor que sea necesaria entre el colectivo o las personas para aumentar el bienestar de todas las personas de la sociedad. El propósito de este ensayo es reflexionar sobre el hombre que experimenta. Es un hombre que conoce, sus experiencias vividas en gran medida lo llevan al enfoque empírico, tema principal del ensayo, que permite reconocerlo como un hombre fruto de la experiencia. Haciendo una lectura comprensiva del ensayo presentado encontrará que los aspectos fundamentales del empirismo tienen validez en la actualidad y se puede experimentar de manera diferente siempre y cuando el aspecto empírico y el proceso teórico validen en su parte explicativa los hechos. Como en el caso de la educación, que se privilegian los procesos empíricos en el proceso enseñanza-aprendizaje.
Keywords: ENFOQUE EMPIRICO; BIENESTAR; TRABAJO SOCIAL